“We are conservative”: protestant ministers, history, and the creation of Southern christian identity, 1830-1865 - Manger, Edward George (Universitätsbibliothek Heidelberg, 2023)
This thesis examines the nature of Southern Christianity in light of its saturation in a culture of history. It argues that white Southern Protestants were steeped in historical thinking during the Antebellum and Civil War periods. The four largest denominations (Baptist, Methodist, Presbyterian and Episcopalian) were deeply engaged in the writing of history, consumption of history and teaching of history. They conceived of themselves historically and invented historic identities that explained their place and purpose in the world. These narratives and stories they told, in books, sermons and periodicals, reveal the way Southern Christians imagined themselves to be people with a storied past. These identities were also shaped the minds of Southern Christians, enabling them to enact a piety molded by historical precedent. It is argued that this phenomenon explains the self perception of Southern Christians, which grew during this period, as a persecuted people, beleaguered, and attacked for the cause of Christ and the way in which that belief related to the defense of racial slavery. The common education in history undergone by ministers also equipped them to use history polemically, to see themselves primarily as the defenders of orthodoxy, the stalwarts of time tested truths, which inevitably framed the debates over slavery, succession, and the Confederacy. These factors, developed during the Antebellum period, contributed to Confederate Civil Religion and Confederate Nationalism, underpinned by a religious historic identity at all points. The Church's voice was heightened and exaggerated by the events of the Civil War, as attempts to explain the conflict with reference to the past and God's grand scheme of history multiplied. Understanding the place of history in each of the Southern denominations, the authority it had, the identities it forged and reinforced, and the way it was deployed and used, explains Southern Protestant Christianity's attitude toward race, and social hierarchy.
Keywords: Hochschulschrift